IBM USAHA PENGGILINGAN PADI - Kholmi, Masiyah (Studi Kasus Inovasi Ekonomi, 2016)
Kedungbetik is an agricultural village and the majority ofthe farmer. Kedungbetik rural community with apopulation of approximately 6,842 person, that potential tomotivate H Taufiq to open a rice mill since 2008. Duringthis time, H. Taufiq financial records have not been doingwell. With such conditions, it is necessary to do thetraining and mentoring the preparation and financialreporting to determine the development of the business.The method used in training and financial reporting aretutorials and interactive method between instructor withpartners and performed assistance in the preparation offinancial statements.The results achieved in the implementation of scienceand technology program for Community (IbM) is activelyPartners financial records, but still a revenue receiptobtained from milled costs minus operating costs. Startingearly 2015 recording financial transactions in a moresystematic and informative, but the cost of electricity,machine depreciation, building and the car expensecomponents not yet included in the cost as a reduction ofrevenue.